Transformasi digital, e-commerce halal, dan partisipasi gen z dalam ekonomi syariah: analisis regulasi dan etika ekonomi - subhi, Irfan (Maliki Interdisciplinary Journal, 2026)
Particularly among Generation Z, who are digital natives and heavily reliant on technology, social media, and e-commerce platforms, digital revolution has drastically altered societal consumption patterns. Simultaneously, the demand for halal goods and services offered in online marketplaces has surged due to the growing trend of the halal lifestyle. Through regulatory and ethical lenses, this study seeks to examine the connections between digital transformation, the growth of halal e-commerce, and Gen Z involvement in the Islamic economy. By looking at pertinent laws, DSN-MUI fatwas, and studies on digital consumption behavior, this study uses a descriptive qualitative methodology. The results show that digital transformation increases Gen Z’s involvement in the Islamic economic ecosystem and increases their access to halal items. However, there are still issues with ensuring that e-commerce activities adhere to syariah contractual principles, product verification, and information transparency in order to comply with halal requirements. Furthermore, Islamic economic norms like avoiding wastefulness and keeping balance frequently clash with Gen Z’s spending habits, which are influenced by digital culture. In order to build a more reliable and long-lasting halal e-commerce environment, this study emphasizes the significance of tightening digital regulations, improving halal literacy, and implementing Islamic consuming ethics.